How adjunct faculty's professional work experience affects the community college learning environment - Beckford-Yanes, Carolyn A., author; Davies, Timothy Gray, advisor; Banning, James H., committee member; Deniston, Terry, committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2005)
Part-time and adjunct faculty have been present in community colleges since its inauguration as a higher education institution. Both groups provide financial savings, flexibility in staffing, and have made significant contributions to community colleges on a variety of levels. Adjuncts tend to be included in the classification of part-time faculty because they teach on a part time basis, however, there is a major distinction between part-time and adjunct faculty. Adjunct faculty are typically those instructors bringing breadth, depth, and relevance to the curriculum who allow colleges to teach subjects that would otherwise be excluded from the curriculum. They provide a strong link to the community and to the workplace, as well as a tried and tested talent pool for recruiting full-time faculty. It is the adjunct faculty that brings real-world experience to the classroom. Specifically, this research looked at adjunct faculty's impact and contribution. Study participants all revealed that adjunct faculty made a significant impact on the college and its students. They are seen as instrumental in preparing students for the job market by bridging the knowledge gap, especially in fields like information and medical technology where data changes rapidly. Students saw adjunct faculty as professionals providing solid industry experience, not just textbook lectures. They were impressed with the availability and accessible of their adjunct instructors who could be reached day or night via phone and email. The expression of empathy and understanding from their adjunct faculty when school and work life conflicted made a difference in their ability to complete or further their education. Contribution was determined to be made on several levels. Participants saw adjunct faculty as experts, specialists, and procurers of industry standards. From their world-of-work, adjunct faculty brought real-life examples into the classroom and were able to aid students in making connection between theory and practice. Administrators hire them because of the strong industry credentials they bring into the classroom and students value them because they are learning cutting-edge data. This study not only confirms that adjunct faculty's professional work experience affects the community college learning environment, but also that community college students value the professional work experience of the adjunct faculty.
Keywords: community colleges; community college education